FERMENTASI UBI KAYU (Manihot utillisima Pohl) DENGAN RAGI Monascus purpureus UNTUK PRODUKSI ZAT WARNA ANGKAK - Rachmat Kosman; Pirman AP; Aco Mappacanda (As-Syifaa Jurnal Farmasi, 2010)
Has conducted research on the cassava (Manihot utillisima Pohl.) fermentation  with Monascus purpureus yeast to angkak essence pigmen production. This research aimed to make angkak pigmen by solid and pigmen extraction from fermentasion using Monascus purpureus. Then the wevelength is measured by using spectrophotometry UV-Vis. The result of research is 30 gram of cassava (Manihot utillisima Pohl.) fermented product obtained angkak dye with yellow dye % levels as much as 36,64%. Where the results of measurements of spectrophotometry UV-Vis showed that the maximum wevelength of 398,0 nm.Key Words : Manihot utillisima Pohl, Monascus purpureus, Angkak